2021
DOI: 10.3390/polym13193348
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Emulsifier-Free Styrene–Acrylic Emulsion via Reverse Iodine Transfer Polymerization

Abstract: Styrene–acrylic emulsions containing hydroxyl functional monomer unit’s component are widely used for maintenance coating. In this paper, a stable emulsifier-free styrene–acrylic emulsion with solid content over 43% could be obtained in 210 min via reverse iodine transfer polymerization (RITP). By adding a mixture of methacrylic acid (MAA) and poly(ethylene glycol)methyl ether methacrylate (PEGMA) into a system containing a high content of hydroxyl functional monomer component (19.4 wt.% of the total monomer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Also, two peaks at 1,452 and 1,379 cm −1 were produced by C–H bending vibrations of –CH 3 and –CH 2 groups, respectively, the peak at 1,727 cm −1 resulted from the stretching vibration of the carbonyl ester C = O and the peak at 1,494 cm −1 due to the asymmetric stretching vibration of carbonyl anion COO−. Asymmetric stretching vibration, symmetric stretching vibration and bending vibration of C–O– C appeared at 1,237, 1,064 and 1,157 cm −1 , respectively (Huang and Gong, 2021). The absence of the peak at 1,680 – 1620 cm −1 of alkenyl C = C stretch confirmed that the polymerization of all monomers was achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Also, two peaks at 1,452 and 1,379 cm −1 were produced by C–H bending vibrations of –CH 3 and –CH 2 groups, respectively, the peak at 1,727 cm −1 resulted from the stretching vibration of the carbonyl ester C = O and the peak at 1,494 cm −1 due to the asymmetric stretching vibration of carbonyl anion COO−. Asymmetric stretching vibration, symmetric stretching vibration and bending vibration of C–O– C appeared at 1,237, 1,064 and 1,157 cm −1 , respectively (Huang and Gong, 2021). The absence of the peak at 1,680 – 1620 cm −1 of alkenyl C = C stretch confirmed that the polymerization of all monomers was achieved.…”
Section: Resultsmentioning
confidence: 99%
“…As a hard monomer, St has a higher T g , while BA acts as a soft monomer. The Fox equation, which explains how a rigid monomer proportion affects the polymer's glass transition, indicates that an increase of hard monomer proportion leads to an increase in T g 41,42 . Therefore, BS3 emulsion with the highest St content possesses the highest T g .…”
Section: Resultsmentioning
confidence: 99%
“…Styrene acrylic emulsions are widely used as coatings for textiles, train cars, ship interiors, buildings, architectural coatings, adhesives, paper coatings, etc. Coatings based on styrene acrylate emulsions display excellent UV stability, resistance to water, detergents, and alkalis, and they have low-volatile organic compounds (VOCs) [31,32]. Although they cannot be utilized alone as fire-retardant materials, they can be used as binders for fire-retardant additives to different substrates with good coating performances [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%